Collapse of the native structure caused by a single amino acid exchange in human NAD(P)H:quinone oxidoreductase1. (19th September 2014) - Lienhart, Wolf‐Dieter; Gudipati, Venugopal; Uhl, Michael K.; Binter, Alexandra; Pulido, Sergio A.; Saf, Robert; Zangger, Klaus; Gruber, Karl; Macheroux, Peter
<x xml:space="preserve">Abstract</x> Human NAD(P)H:quinone oxidoreductase 1 (NQO1) is essential for the antioxidant defense system, stabilization of tumor suppressors (e.g. p53, p33, and p73), and activation of quinone‐based chemotherapeutics. Overexpression of NQO1 in many solid tumors, coupled with its ability to convert quinone‐based chemotherapeutics into potent cytotoxic compounds, have made it a very attractive target for anticancer drugs. A naturally occurring single‐nucleotide polymorphism (C609T) leading to an amino acid exchange (P187S) has been implicated in the development of various cancers and poor survival rates following anthracyclin‐based adjuvant chemotherapy. Despite its importance for cancer prediction and therapy, the exact molecular basis for the loss of function in NQO1 P187S is currently unknown. Therefore, we solved the crystal structure of NQO1 P187S. Surprisingly, this structure is almost identical to NQO1. Employing a combination of NMR spectroscopy and limited proteolysis experiments, we demonstrated that the single amino acid exchange destabilized interactions between the core and C‐terminus, leading to depopulation of the native structure in solution. This collapse of the native structure diminished cofactor affinity and led to a less competent FAD‐binding pocket, thus severely compromising the catalytic capacity of the variant protein. Hence, our findings provide a rationale for the loss of function in NQO1 P187S with a frequently occurring single‐nucleotide polymorphism. Database Structural data are available in the Protein Data Bank under the accession numbers 4cet (P187S variant with dicoumarol) and 4cf6 (P187S variant with Cibacron blue). Structured digital abstract NQO1 P187S and NQO1 P187S bind by nuclear magnetic resonance (View interaction) NQO1 P187S and NQO1 P187S bind by x-ray crystallography (1, 2) NQO1 and NQO1 bind by molecular sieving (1, 2)